El sedentarismo nómada : The Sedentarism-Nomad - Rengifo Carpintero, John Alexis; Pinillo, Elena Maritza; Díaz Caicedo, Carmen Helena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
This paper is an argumentatively critic investigation, which moves between paradoxes. We describe the current trend in the society like pathological and dehumanizing. We called this tendency as nomadic-sedentary, which is the first paradox, that is just, the man's tendency to be sedentary of a space or a technological fashion object. Through this object, the man is able to meet the world, just making a click, without leaving your home or workplace, but... traveling the world. This trend is given in between actors socially characterized by plural-narratives-singularities, which is the second paradox, which in turn is due to the politic homogenization, i.e. a process of massive social standardization, a trade ethic, or a regulation process and typical behavior on the logic marketing as introduction of a new way of relating with life, with yourself and the others, i.e. a business relationship, as expressions of an audio-visual pornographic culture, which is the other consumption object, making a pedagogy of consumerism, i.e. a culture and education for buying and selling through technological fashion objects. The last paradox, is the consideration of a tragic and senseless world, which you have to find him rationale. This social scene make the man in the one thing that can to be institutionally... just a consumer goods and a prostituted object.